A cross-sectional study of the association between circulating sex hormone-binding globulin levels and selected adipokines in women with polycystic ovary syndrome - Ciura, Dariusz; Owczarek, Aleksander Jerzy; Franik, Grzegorz; Kocełak, Piotr; Markuszewski, Leszek; Madej, Paweł; Chudek, Jerzy; Olszanecka-Glinianowicz, Magdalena (Frontiers in Medicine, 2023)
Introduction: Changes in the proportion of pro-inflammatory and anti-inflammatory adipokines may reflect accumulation of lipid in the liver and development of insulin resistance.Both liver steatosis and insulin resistance result in decreased sex hormone-binding globulin (SHBG) synthesis. The study aimed to analyze associations between circulating SHBG and adipokines levels in women with polycystic ovary syndrome (PCOS).A cross-sectional cohort study involved 87 women with phenotype A of PCOS (39 normal weight and 48 obese). Body mass, height and waist circumference were measured and BMI was calculated. In addition, body composition was assessed using the bioimpedance method. Serum SHBG levels and plasma apelin-36 and -12, adiponectin, leptin, omentin-1 and RBP-4 were determined by ELISA. Study women were divided into subgroups with SHBG concentrations above and below this lower limit (N=35 (40.2%) and N=52 (59.8%), respectively).The median adiponectin, apelin-12 and apelin-36 levels were significantly lower and leptin levels significantly higher in the subgroup with low SHBG levels than in the subgroup above the lower limit of reference range. While, there were no differences in median omentin-1and RBP-4 between study subgroups. There were positive correlations between SHBG and omentin, adiponectin, apelin-36 and -12 levels as well as negative with leptin levels. However, after adjustment by BMI, waist circumference and body fat percentage only association between SHBG and omentin-1, remained significant.Our results show associations between circulating SHBG and adipokine levels in women with PCOS, and support the role of hormonal disfunction of adipose tissue in the pathogenesis of PCOS.